2021
DOI: 10.1038/s41598-021-83461-0
|View full text |Cite
|
Sign up to set email alerts
|

Extracts of select endemic plants from the Republic of Mauritius exhibiting anti-cancer and immunomodulatory properties

Abstract: Mauritius Island possesses unique plant biodiversity with a potential reservoir of biologically active compounds of pharmacological interest. In the current study, we investigated Mauritius endemic plant families Asteraceae, Ebenaceae, Sapotaceae, and Erythroxylaceae, for anti-cancer properties on T cell lymphoma and B16F10 Melanoma cells and immunomodulatory properties on primary T and B cells. The cytotoxicity of methanolic plant extracts at 1, 10, 25 µg/ml was determined. The most active plant species were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Other immune cell infiltration analyses reported a positive link between the expression levels of CD3D and infiltration of various immune effector cells, including B cells, CD4 + T cells, and CD8 + T cells. B cells and T cells are the major players in the adaptive immune response [ 38 ]. In addition, immune cell infiltration is an indication of the host immune response to cancer antigens [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other immune cell infiltration analyses reported a positive link between the expression levels of CD3D and infiltration of various immune effector cells, including B cells, CD4 + T cells, and CD8 + T cells. B cells and T cells are the major players in the adaptive immune response [ 38 ]. In addition, immune cell infiltration is an indication of the host immune response to cancer antigens [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kauroo et al investigated Mauritius endemic plants (Psiadia lithospermifolia, plants from the Asteraceae family) for anticancer activities in T-cell lymphoma and melanoma cells. They also found that plant extract components have potential anticancer activities in vitro studies [25]. Plant tuber extract (Dioscorea alata var.…”
Section: Introductionmentioning
confidence: 97%
“…For example, in search for anti-cancer activity, cell lines could be treated with a series of plant extracts, followed by testing in speci c screening systems, such as assessment of cell viability. 2,3 Extracts that cause a signi cant killing of cancer cells are selected for further evaluation.…”
Section: Introductionmentioning
confidence: 99%